KEMAMPUAN LITERASI TEKNOLOGI SISWA KELAS X IPS DALAM PEMBELAJARAN GEOGRAFI PADA MATERI DINAMIKA ATMOSFER DAN PENGARUHNYA BAGI KEHIDUPAN DI SMAN 1 PARIAMAN - Savira Tri Darmayanti (JURNAL BUANA, 2022)
This study aims to determine the technological literacy skills of class X IPS students at SMAN 1 Pariaman in learning geography about the dynamics of the atmosphere and its effects on life. This study was conducted with a quantitative approach assisted by descriptive method, using a random sampling technique, with a research sample of 52 students of class X IPS at SMAN 1 Pariaman. This study was carried by distributing questionnaires to the research object. According to the research found the result that the technological literacy abilities of class X IPS students on geography learning in the dynamics of the atmosphere and its effect on life for per indicator, namely on content indicators with a percentage of 76% which is categorized as good, process indicators with a percentage of 78% which is categorized as good, context indicators with a percentage of 76% which is categorized as good, and an indicator of attitude with a percentage of 80% which is categorized as good. So, that overall the students technological literacy skills are classified as good with a total percentage o 77%f.